2002
DOI: 10.1111/j.1749-6632.2002.tb02980.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Course of Disease in Type 1 Diabetes and Islet Cell Antibodies

Abstract: The aim of this study was to estimate the possibility of predicting the course of type 1 diabetes. We analyzed the importance of islet cell antibody levels and residual β cell function in 46 newly diagnosed patients with diabetes. Islet cell antibodies (ICAs; Juvenile Diabetes Foundation [JDF] units) were determined at the time of diagnosis by the indirect immunofluorescent method. β cell function was estimated by C peptide levels (nmol/L) before and after glucagon stimulation at the time of clinical remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
9
1
2
Order By: Relevance
“…Biochemical autoantibody measurements have become the mainstay for identifying autoimmune disease in patients with diabetes (28). The threshold for a positive response in these assays has been set to have a falsepositive rate of Ͻ1% in normal control subjects, and previous DASP workshops have shown that the median adjusted sensitivity for anti-GAD antibody was 84% and for ICA512 was 58%; all GAD65 and ICA512 assays found significant differences between patients and control subjects in that workshop (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical autoantibody measurements have become the mainstay for identifying autoimmune disease in patients with diabetes (28). The threshold for a positive response in these assays has been set to have a falsepositive rate of Ͻ1% in normal control subjects, and previous DASP workshops have shown that the median adjusted sensitivity for anti-GAD antibody was 84% and for ICA512 was 58%; all GAD65 and ICA512 assays found significant differences between patients and control subjects in that workshop (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, measurement of insulin in the peripheral blood does not accurately reflect endogenous insulin secretion. Most studies have approximated insulin secretion with C-peptide levels measured when fasting, at random, or following provocation with mixed meals or glucagon (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). While glucagon produces a reliable insulin response, it does not simulate normal physiology while a mixed meal is physiological.…”
mentioning
confidence: 99%
“…There is some evidence that higher number of detectable autoantibodies is related to more aggressive β-cell destruction and shorter duration of remission [24,30]. Participants were limited to hospital in-patient which may have introduced selection bias.…”
Section: Discussionmentioning
confidence: 99%